Influence of Pigskin on Salmonella Contamination of Pig Carcasses and Cutting Lines in an Italian Slaughterhouse - Bonardi, Silvia (Ital J Food Saf, 2016)
Ninety pig carcasses and twenty one food contact surfaces (FCSs) were tested for Salmonella in a slaughterhouse processing ca. 380 pigs/h between 2014-2015. Sampling was performed during seven sessions. Four carcass sites of 100 cm(2) each (back, belly, jowl externally, and the diaphragmatic area internally) were swabbed after evisceration. Meat conveyors and dressing tables were tested swabbing areas of 200 to 400 cm(2). After pre-enrichment in buffered peptone water, samples were tested by Salmonella MDS(®) assay and the presumptive positives were confirmed by the ISO 6579 method. Salmonella isolates were serotyped following the Kauffman-White-Le Minor scheme and genotyped by XbaI pulsed field gel electrophoresis. Salmonella was isolated from 16/90 [17.8%; confidence interval (CI) 95%=11.2-26.9] carcasses and 4/21 (19.0%; CI 95%=7.7-40.0) FCSs. Four serovars were identified on carcasses. S. enterica 4,[5],12:i:-was the most prevalent (43.75%), followed by S. Rissen (31.25%), S. Derby (12.5%) and S. Bovismorbificans (12.5%). Two serovars were found on FCSs, namely S. Derby (75%) and S. Livingstone (25%). During one sampling session, a failure in carcass dehairing occurred and caused significantly higher prevalence of carcass contamination (60%) than in the remaining sessions. Moreover, in the same session, Salmonella prevalence was marginally significantly higher on FCSs than in the remaining sampling days, suggesting that dehairing affects contamination not only on carcasses, but also on the working surfaces.